Error Compensation Strategy for Roll Gap of Roller Crusher Based on Adaptive Reference Model. (September 2020) - Yang, Yinwei; Fan, Kai
Abstract: Roll gap between the two rollers of crusher is adjusted constantly to satisfy the particle size of output material. In order to realize convenient adjustment, a roll gap control scheme based on hydraulic technology is designed and optimized in this paper. And an adaptive reference model is applied to compensate synchronous error of the rollers. Then simulation model and algorithm structure are elaborated subsequently. Finally, an experiment platform is built to validate the performance of the proposed approach.